2018
DOI: 10.1111/cea.13161
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy with omalizumab reverses the Th2 cell‐like programme of regulatory T cells and restores their function

Abstract: OIT supplemented by omalizumab promotes allergen desensitization through an initial omalizumab-dependent step that acutely depletes allergen-reactive T cells, followed by an increase in allergen-specific Treg cell activity due to the reversal of their Th2 cell-like programme. Improved Treg cell function may be a key mechanism by which OIT ameliorates food allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 40 publications
(99 reference statements)
1
29
0
2
Order By: Relevance
“…The subverted TH2‐like Treg cells play a critical role in disease pathogenesis under conditions of TH2‐high inflammation induced, including paradigms of food allergy (FA) and allergic airway inflammation induced in Il4ra F709 mice . A similar phenotype is seen in human subjects with FA, indicating that this subversion is operative in human allergic disorders . A more sharply restricted Treg cell TH2 cell‐like response can aid in providing protection against helminths by generating TH2 cell‐like ex‐Treg cells that add to the TH2 response …”
Section: Il‐4r Signalling In Tolerance Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The subverted TH2‐like Treg cells play a critical role in disease pathogenesis under conditions of TH2‐high inflammation induced, including paradigms of food allergy (FA) and allergic airway inflammation induced in Il4ra F709 mice . A similar phenotype is seen in human subjects with FA, indicating that this subversion is operative in human allergic disorders . A more sharply restricted Treg cell TH2 cell‐like response can aid in providing protection against helminths by generating TH2 cell‐like ex‐Treg cells that add to the TH2 response …”
Section: Il‐4r Signalling In Tolerance Modulationmentioning
confidence: 99%
“…Abdel‐Gadir et al found that treatment of lymphocytes peanut‐allergic patients with anti‐IL‐4Rα mAb augmented the suppressive function of peanut‐reactive Treg cells, highlighting the potential disease‐modifying effect of anti‐IL4 therapy . Recently, Rial MJ et al have presented a case report showing a very successful therapy of newly developed food allergy to corn and nuts using Dupilumab .…”
Section: Dupilumab For Food Allergymentioning
confidence: 99%
“…As there is limited data on the sustainability of desensitization of multifood-OIT [ 23 , 24 ], Andorf et al conducted a multisite multifood-OIT study to compare the efficacy of successful desensitization with sustained dosing vs discontinued dosing after multifood-OIT [ 25 ]. Results suggested that sustained desensitization after multi-OIT best occurs through continued maintenance OIT dosing of either 300 mg or 1 g of each food allergen as opposed to discontinuation of multi-OIT.…”
Section: Oral Immunotherapymentioning
confidence: 99%
“…With regard to the mechanism of action, in oral immunotherapy for food allergy (which, although not accepted in guidelines, has been used by some authors for desensitization to food allergy), one study demonstrated that supplementing treatment with omalizumab resulted in specific desensitization to the administered food, with an initial omalizumab-dependent depletion of allergen-reactive T cells and subsequent increase in allergen-specific T-regulatory cells that induced the reversal of Th2 cell-like activity. 69 It is unlikely that this mechanism of action is limited to food-allergy immunotherapy supplemented with omalizumab, and may also work in other forms of immunotherapy in combination with omalizumab.…”
Section: Issues To Be Investigated In Omalizumab Treatmentmentioning
confidence: 99%